Adaptation to climate change in pastoral communities: a systematic review through a social-ecological lens - Matilda Azong Cho; Onisimo Mutanga; Tafadzwanashe Mabhaudhi (International Journal of Climate Change Strategies and Management, 2024)
Purpose – This paper aims to apply a socio-ecological systems framework to demonstrate that pastoral adaptation to climate change necessitates a comprehensive approach. Design/methodology/approach – The authors evaluated the depth of knowledge regarding pastoral adaptation in Africa using bibliometric and content-based analyses. Findings – The analysis of 40 eligible articles, conducted through R Studio, revealed a significant emphasis on climate change adaptation measures. However, there was a noticeable scarcity of research on the role of governance, policy and institutional interventions. Research limitations/implications – The scope of the research is limited to the African continent. Practical implications – This research shed light on how inadequate governance structures and insufficient institutional support, particularly in terms of skills and capacity-building, hinder pastoral communities’ resilience. These limitations may potentially affect pastoral livelihoods adversely, with severe consequences for food security and poverty levels in Africa. Social implications – A comprehensive understanding of the challenges pastoralists face in Africa to adapt to climate change will assist in defining high-level policies and interventions to improve pastoral communities’ adaptation actions. Originality/value – The study used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses approach to ensure a thorough and systematic investigation. Furthermore, using an established framework and clearly defined methods will greatly aid in replicating the research.